Dealer's perception on various brands of agrochemical products and their promotional activities in nalgonda district of telangana state - Y. RADHA, VIVEKANANDA REDDY, SEEMA and (The Journal of Research, PJTSAU, 2017)
Indian economy is largely agrarian in nature, which is contributing about one fifth of the total GDP. The occupation of nearly 58 per cent of the populationis agriculture. Since a decade, India’s population is on increasing note therefore, to meet the food grain requirement for the increasing population, there must be intensive agriculture with judicious use of inputs like fertilizers, pesticides, seeds, irrigation etc. In view of the fact that nearly 30 per cent of the potential food production is lost in India due to the damage caused by the insect pest, plant pathogens, weeds, rodents, birds etc., so the use of pesticides has become absolutely essential . Hence, the agrochemicals industry in India has a vital role in the economy of the country.